Integrated Nano-Biomechanics - Yamaguchi, T. (Takami), 1948- (Micro & nano technologies., 2018)
"Integrated Nano-Biomechanics provides an integrated look into the rapidly evolving field of nanobiomechanics. The book demystifies the processes in living organisms at the micro- and nano-scale through mechanics, using theoretical, computational and experimental means. The book develops the concept of integrating different technologies along the hierarchical structure of biological systems and clarifies biomechanical interactions among different levels for the analysis of multi-scale pathophysiological phenomena. With a focus on nano-scale processes and biomedical applications, it is shown how knowledge obtained can be utilized in a range of areas, including diagnosis and treatment of various human diseases and alternative energy production. This book is based on collaboration of researchers from a unique combination of fields, including biomechanics, computational mechanics, GPU application, electron microscopy, biology of motile micro-organisms, entomological mechanics and clinical medicine. The book will be of great interest to scientists and researchers involved in disciplines, such as micro- and nano-engineering, bionanotechnology, biomedical engineering, micro- and nano-scale fluid-mechanics (such as in MEMS devices), nanomedicine and microbiology, as well as industries such as optical devices, computer simulation, plant based energy sources and clinical diagnosis of the gastric diseases. Provides knowledge of integrated biomechanics, focusing on nano-scale, in this rapidly growing research field Explains how the different technologies can be integrated and applied in a variety of biomedical application fields, as well as for alternative energy sources Uses a collaborative, multidisciplinary approach to provide a comprehensive coverage of nano-biomechanics"--